Odontaster validus Koehler 1905 ... - Jangoux, Michel (Zenodo, 2022)
tenuis Koehler, 1905, Odontaster Odontaster tenuis Koehler, 1905: 468; 1906: 8, pl. 4, figs 33-38. Odontaster validus ‒ Clark 1993: 198. CURRENT STATUS. — Odontaster validus Koehler, 1905. TYPE MATERIAL. — Antarctic • 1 syntype; Howgard Island; French Antarctic expedition; 1903-1905; MNHN-IE-2014-203 • 4 syntypes; same as for preceding; MNHN-IE-2014-335 • 1 syntype; unspecified locality; same as for preceding; MNHN-IE-2014-211 • 5 syntypes; same as for preceding; MNHN-IE-2014-236 • 1 syntype; same as for preceding; MNHN-IE-2014-445. REMARK Koehler (1906) mentions nine specimens:five were collected in Howgard Island waters, the origin of the others is unspecified. ... : Published as part of Jangoux, Michel, 2022, The type specimens of extant asteroids (Echinodermata) in the Muséum national d'Histoire naturelle of Paris, pp. 259-334 in Zoosystema 44 (11) on page 320, DOI: 10.5252/zoosystema2022v44a11, http://zenodo.org/record/6616817 ...